Mudanças de preferências do consumidor em um cenário de pandemia - Marinho, Louryval Passos de Oliveira (Brasil, 2023)
This work will to investigate, through a questionnaire carried out with 148 students of the Economic Sciences course at the Federal University of Amazonas, whether the COVID-19 Pandemic had implications in the consumption decision-making process. Using an online questionnaire in which two hypothetical scenarios were also prepared in which there are two baskets of goods for consumers to choose from, one with access to price information and the other not, to detect whether the pandemic has led to changes in consumer preferences. students. As it is a qualitative variable, it was necessary to use a probabilistic model of the logit regression type, obtaining as a response the probability of the consumer opting for one basket over another. So that it was possible to verify, among the chosen coefficients, which one is significant to estimate the probability of consumer choice, concluding that in a context of a Pandemic, preferences are influenced by the prices of goods and income level.